A phase 2 study of tremelimumab in patients with advanced uveal melanoma. Issue 4 (August 2015) - Joshua, Anthony M.; Monzon, Jose G.; Mihalcioiu, Catalin; Hogg, David; Smylie, Michael; Cheng, Tina
Abstract : Similar to cutaneous melanoma, several strategies of immune escape have been documented in uveal melanomas (UMs). We hypothesized that these cancers could respond to cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) inhibition with tremelimumab by potentiating T-cell activation. This was an open-label, multicentre phase 2 study in patients with advanced UM who had not received prior immunotherapy. Patient received tremelimumab at 15 mg/kg administered every 90 days for up to four cycles. The primary endpoint was 6-month progression-free survival (PFS). Secondary endpoints were safety, durable response rate, objective response rate, duration of objective response, duration of complete response, and median overall survival (OS). Eleven patients, all with M1c disease, were enrolled with no responses observed. The median follow-up was 11 months (range 2–36 months). The median PFS was 2.9 months (95% confidence interval 2.8–3.0) and the 6-month PFS rate was 9.1%. The median OS was 12.8 months (95% confidence interval 3.8–19.7). Toxicities were consistent with CTLA-4 blockade and were manageable. Although the median OS of 12.8 months and the manageable toxicity profile of tremelimumab observed in this study seem promising, the modest 6-month PFS and the lack of responses observed resulted in the study being stopped due to futility at the first interim stage. To date, no systemic treatment has demonstrated a survival benefit in patients with advanced UM. The standard treatment for patients with advanced UM should be a clinical trial.